Perancangan Sistem Informasi Pendaftaran Online Pada Sekolah Sepak Bola Indonesia Muda Legok Berbasis Web - Mochamad Azi Haetami; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
At legok young Indonesian football schools, prospective participants who will apply still use paper forms. As well as the process of collecting players / students still using books, as well as training schedules still using books. In addition, to fill the schedule of football matches still have to write in the writing / book. On the registration of new students, the new student form often occurs as a result in the administrative process is still not neat because it has not used the database so that the school asks to refill the form again. Research methods are descriptive, namely research that solves an existing problem based on analysis and interpretation data. The analysis method used is the waterfall model. The waterfall model is often also called the linear sequential model or classic life cycle. The waterfall model provides a sequential or sequential approach to software life flow starting from analysis, design, coding, testing, and support stages. With the online registration information system at legok young Indonesian football schools, the public no longer needs to come directly to the football school, but can already register online through the web Online registration information system at young Indonesian football schools legok community or players can find out more easily about legok young Indonesian football schools.